2007
DOI: 10.1002/elan.200704005
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated Graphite Oxide Modified Electrode for the Selective Determination of Picomolar Concentration of Lead

Abstract: We report the selective, picomolar determination of lead(II) ions using exfoliated graphite oxide (EGO) modified glassy carbon electrode. Exfoliated graphite oxide is the oxidized form of exfoliated graphite containing a variety of functional groups such as hydroxyl, phenolic and carboxyl groups. The EGO can be dispersed as a stable colloid in a wide range of pH, from 2 to 11. This leads to the flexibility of film formation on substrates and use of a variety of functional groups to complex lead ions. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…The unmodified glassy carbon spheres have revealed the presence of peaks due to -OH and CQO groups of -COOH at 3435 and 1600 cm À 1 , respectively. The peak at 1351 cm À 1 might be due to the stretching of -OH group of phenol, and the peak at 2800 cm À 1 is due to the stretching of aromatic protons which are in good agreement with the reported literature [18]. However, the IR spectrum of the modified glassy carbon spheres showed peaks at 1618 and 3336.4 cm À 1 , revealing the presence of CQO and -NH groups of amide bond.…”
Section: Resultssupporting
confidence: 90%
“…The unmodified glassy carbon spheres have revealed the presence of peaks due to -OH and CQO groups of -COOH at 3435 and 1600 cm À 1 , respectively. The peak at 1351 cm À 1 might be due to the stretching of -OH group of phenol, and the peak at 2800 cm À 1 is due to the stretching of aromatic protons which are in good agreement with the reported literature [18]. However, the IR spectrum of the modified glassy carbon spheres showed peaks at 1618 and 3336.4 cm À 1 , revealing the presence of CQO and -NH groups of amide bond.…”
Section: Resultssupporting
confidence: 90%
“…However in the subsequent reverse scan, the voltammogram showed two peaks at −0.49 and −0.75 V which corresponds to the reoxidation of lead and cadmium ions, respectively. The redox potential of Pb 2+ is in agreement with the literature [21] and the peaks at −0.87 and −0.75 V might be due to the reduction and oxidation of Cd 2+ ions, respectively. In case of oxidized and modified electrode there is a small increase in the capacitive current when compared to unmodified electrode.…”
Section: Voltammetry Of Pb 2+ and CD 2+ Ions At Salicylic Acid Modifisupporting
confidence: 89%
“…These observations have revealed that the presence of modifier molecule with suitable functionalities could enhance the electrochemical response for both lead and cadmium ions. This kind of modified electrode behavior might be attributed to the interacting ability of the functional groups i.e., carboxyl and hydroxyl present on the surface of carbon toward lead and cadmium ions present in the electrolyte at the interface [21].…”
Section: Voltammetry Of Pb 2+ and CD 2+ Ions At Salicylic Acid Modifimentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the carbon powder particles were washed with acetone to remove the moisture. The functionalized carbon powder was dried by placing in a fume hood for a period of 10 h and stored in an airtight container prior to its use [44] (Scheme 2).…”
Section: Covalent Modification Of Graphitic Carbon With Amino-calixarenementioning
confidence: 99%